Carbon monoxide levels in the expired air of smokers - Türkcan, Ahmet; Çakmak, Duran (Journal of Dependence, 2004)
Objective: There are a variety of independent methods of estimating smoking status. The measurement of carbon monoxide in the expired air has proven to be a reliable and convenient method. The purpose of this study is to determine the optimal breath carbon monoxide concentration cut-off level to distinguish actual smokers from nonsmokers. Method: A hand held breath analyzer (Micro CO) was used to measure expired-air carbon-monoxide concentrations. Breath carbon monoxide levels were measured in 31 smokers and 30 nonsmokers. Results: The range of carbon monoxide concentrations obtained was 0-5 parts per million (ppm) in the non-smoking group and 5-70 ppm in the smoking group. Smokers had a mean breath carbon monoxide concentration of 27.8 + 17.0 ppm and non-smokers had a mean of 1.7 +1.0 ppm (p<0.01). Mean breath carbon monoxide concentrations increased in direct proportion to the number of cigarettes smoked (p<0.01). The optimal cut-off level of breath carbon monoxide to discriminate between actual smokers and nonsmokers was 5 ppm with 96.8 % sensitivity and 96.7 % specifity. Conclusion: Breath carbon monoxide concentration provides an easy, noninvasive, and immediate way of assessing a patient’s smoking status. Micro CO analyzer is a portable and practical analyzer for measuring expired-air carbon monoxide. A reading > 5 ppm strongly suggests that a person is a smoker.